Liquid-like grain boundary complexion and sub-eutectic activated sintering in CuO-doped TiO2. (15th May 2017) - Nie, Jiuyuan; Chan, Jonathan M.; Qin, Mingde; Zhou, Naixie; Luo, Jian
Abstract: The eutectic temperature and composition of the TiO2 -CuO system were carefully measured to be 1010 ± 10 °C and 83CuO:17TiO2, respectively. Subsequently, a TiO2 -CuO phase diagram was computed, representing a correction and major improvement from the phase diagram available in literature. Dilatometry measurements and isothermal sintering experiments unequivocally demonstrated the activated (enhanced) sintering of TiO2 with the addition of CuO, occurring at as low as >300 °C below the eutectic temperature. High resolution transmission electron microscopy (HRTEM) characterization of water-quenched specimens revealed the formation of nanometer-thick, liquid-like, intergranular films (IGFs), a type of grain boundary (GB) complexion ( a.k.a. 2-D interfacial phase), concurrently with accelerated densification and well below the bulk eutectic temperature. Consequently, activated sintering is explained from the enhanced mass transport in this premelting-like complexion. An interfacial thermodynamic model was used to quantitatively explain and justify the stabilization of liquid-like IGFs below the eutectic temperature and the temperature-dependent IGF thicknesses measured by HRTEM. A GB λ diagram was computed, for the first time for a ceramic system, to represent the thermodynamic tendency for general GBs in CuO-doped TiO2 to disorder. Graphical abstract: Image Highlights: A refined TiO2 -CuO phase diagram was developed. Sub-eutectic activated sintering was verified and explained. HRTEM observed a liquid-like grain boundary complexion. A model developed for premelting-like intergranular films. The first ceramic grain boundary λ diagram was computed.